Wydział Teologiczny Uniwersytetu Mikołaja Kopernika w Toruniu - Perszon, Jan (Studia Nauk Teologicznych PAN, 2020)
Th e Department was established at the University of Nicolas Copernicus on October 1st, 2001. Its faculty members were recruited from among the theologians working in two diocesan Seminaries – in Torun and in Włocławek. The fi rst dean was prof. dr hab. George Bagrowicz. His successor, prof. dr hab. John Perszon was elected in 2005, to be then reelected in 2008. Currently, the Department comprises forty two full-time faculty members who specialize in various theological disciplines. Th ere are 480 students. Th e Department off ers graduate degrees, i.e., master’s and doctoral degrees. Students can choose from among four diff erent specializations: priestly, pastoralcatechetic, “Caritas” social work and studies on the family. Th e programs operate with the Polish grading system as the formal grading, but students are also graded according to the ECTS grading scale. One of the highest priorities of the Department has always been promoting international cooperation with other centers of theological studies. Among them, especially three are to be mentioned: Th e School of Th eology of the University of Navarra (Spain), Katolisch-Th eologische Fakultät of the University of Würzburg (Germany), Th e Department of Th eology of the Vytautas Magnus University (Lithuania). Conferences attended by foreign theologians have been organized in Torun and our faculty members actively participated in conferences organized abroad. Th e main academic periodical of the Department is “Teologia i Człowiek” (“Th eology and Man”). Th ere are also four theological series where members of the Faculty publish their papers: Euntes Docete, Scripta Th eologica Th orunensia, Biblia et Patristica Th orunensia and Series Biblica Paulina. In cooperation with the Department of Pedagogy another semi-annual journal “Paedagogia Christiana”. Among the most recent academic projects created by the Department of Th eology is an online collection of biblical articles www.biblistyka.umk.pl). It is an indispensible means for research for all Polish theologians. Th e project is entirely sponsored by the University of Nicolas Copernicus.